Surgical Safety Checklist: An essential tool to increase patient safety (Journal of Society of Surgeons of Nepal, 2020)
Medical practice without surgery cannot be assumed in the present context. Surgery is the need for individual and safety is his/her right. To increase the safety of the patient by overcoming medical errors, the WHOfirst introduced the Surgical Safety Checklist more than a decade back. It can be modified as per local needs. Its relevance is seen increasing day by day. When we hear about surgical errors, it is usually felt that it couldhave been prevented if the checklist were used properly. Teamwork and commitment is a must along with the proper definition of roles of each individual involved in the team. Surgery cannot be considered complete until the safe discharge of the patient is done. Many surgical errors can be prevented by its consistent use. Its use should come as a reflex rather than considering it to be a burden to the existing workload.